The Pathways Involved in TLQP-62 Mediated Biological Functions: A Review - Akhter, Md. Shamim; Arif, Jojon (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2018)
VGF is neurosecretory protein, belongs to the extendedgranin family of proteins, originallyrecognized as a nerve growth factor (NGF) inducible gene product. It is selectively synthesized mostly in neuronal and neuroendocrine cells. It has a very simple organization. It has several biologically active peptides, described as VGF-derived peptides including APPG-40, APPG-37, GRPE-37, NERP-1, NERP-2, NAPP-129 (VGF 20), VGF 18, HFHH-51 (VGF 6), HHPD-1, AQEE-30 (Peptide V), LQEQ-19, TLQP-21 and TLQP-62 (VGF 10). Among these peptides TLQP-62 is of great significance because of its several remarkable biological effects like regulation of memory formation, glucose homeostasis and insulin secretion, gene transcription, neurogenesis, etc. Although in light of these outstanding behavioral and physiological roles, very few information are available regarding its mode of action. Still, no receptor has been found for TLQP-62 mediated cascading pathways. However, considering the significant biological function of TLQP-62, this review study was done to summarize the pathways involved in TLQP-62 mediated action, based on the information till now. TLQP-62 activates signal transduction cascades by two mechanisms including opening of the calcium channels and modulating the AMPK, PKC and ERK pathways. These events result in an increase in intracellular Ca2+ concentration which permits the secretion of insulin. TLQP-62 would be a significant therapeutics and drug discovery tool for a wide range of diseases to which the peptide related, if TLQP-62 mediated pathways are known, as a whole.